PENGEMBANGAN PROFESIONALISME GURU DI MAS PONDOK PESANTREN AL-QOMARIYAH - Br Barus, Ratih Alinda; Rohman, Fatkhur (Dharmas Education Journal (DE_Journal), 2023)
Within the framework of KTSP implementation, teacher professionalism is demanded to be able to build learning experiences for their students. Teacher professionalism is not only measured by the suitability of subjects with their fields of study. In the effort to develop national education, an adequate number of teachers is needed with guaranteed quality standards of competence and professionalism. Professionalism is determined as a competency that meets professional education standards so that teachers are required to have a professional background that has consequences as a principle of professionalism. Teacher professionalism in the educational process is one of the important keys to student learning success. Professional teachers are basically determined by their attitude which means at the level of maturity that requires willingness and ability, both intellectually and in excellent condition. Professionalization must be seen as a continuous process. In simple terms, the purpose of this research is to find out the extent to which the professionalism of teachers at MAS Pondok Pesantren Al-Qomariyah, Dusun II Kotangan, Kec Galang. While the specific purpose of this research is to describe: 1). Teacher Professionalism Development 2). professional development strategy.